Offsetting N2O emissions through nitrifying CO2 fixation in grassland soil. (February 2022) - Xia, Weiwei; Bowatte, Saman; Jia, Zhongjun; Newton, Paul
Abstract: This paper presents data on the net greenhouse gas balance (measured as CO2 equivalents) of N2 O emitted and C fixed in nitrifying pastoral soils over a 10-week laboratory incubation period. In a low nitrogen environment without urine deposition, typical of large areas of grassland, archaeal-dominated nitrification increased soil organic carbon (SOC) to the point that these offset N2 O emissions. In a very high N environment typical of urine patch, where bacteria dominated nitrification, N2 O emissions were offset by C fixation for 3 weeks but were then overwhelmed by a rapid increase in N2 O production. Given the very large area of grasslands globally and the importance of nitrification in grassland soils, our finding provides a basis for re-evaluating the budget for net greenhouse emissions from grassland. Highlights: Nitrifiers can fix sufficient CO2 to offset the greenhouse effect of N2 O produced during nitrification in low N areas. Archaea dominated nitrification-mediated CO2 fixation in low N areas. At very high N, such as a urine patch, N2 O exceeds CO2 fixation during nitrification.